Parents in Prison and Their Minor Children: comparisons Between State and National Estimates - Shlafer, Rebecca (The prison journal, 2019)
To estimate the number of parents in state prisons in Minnesota, 2,242 adults completed a brief survey. More than two thirds reported having minor children. More women than men reported being a parent; over half reported living with their children before arrest. In a multivariate model, parent gender, residing with children pre-incarceration, and child age predicted interest in parenting programming. The current study yielded a higher prevalence of parental incarceration than national and other state estimates. Findings underscore the importance of documenting the prevalence of parents in prison and identifying programs and policies to address their needs.